Interações Agroecológicas: a comunidade de São Pedro de Cima em movimento - Nathan Zanzoni Itaborahy (2014)
This dissertation is focused on territorial and productive issues regarding the quilombola community of São Pedro de Cima, in the municipality of Divino, Zona da Mata of Minas Gerais state. Since the year 2009 the EWÉ Group (UFJF) performs their research and extension in the community, committed to the collective construction of agroecological transition, seen as a slow process of articulation between farmers and social organizations for social and environmentally fairer agriculture. To this end, it was proposed a study of the local territorial dynamics, which was based on our theoretical considerations on the concepts of place and territory, both were thought from a geography in motion, interested in subaltern territorialities, invisibilized by an eurocentric historiography and the modern-colonial science. Intending to build a deeper look into the actual production and the conflicts it involves, we understand agriculture as a complex cutout of research and hence, questions environmental, cultural, economical and production issues. With this study it was possible to understand with some clarity the impositions of agricultural modernization in the community, their consequence on the daily lives of peasant, who now have coffee plantation as their flagship, dependent on the use of agricultural inputs and pesticides. It was also possible to better understand the resistance to this model, the quilombolans and peasants knowledge materialized in the bonds of parentage and solidarity, on the productive diversity of backyards and experiences of diversification of coffee plantations. Moreover, we try to expose our extension actions with residents, which were conspicuous by dialogue and community participation, these being the methodological foundations of the work. The EWÉ group met with other actors of the regional agroecological movement, overall the Sindicato dos Trabalhadores e Trabalhadoras Rurais de Divino (local social organization of rural workers) and the Centro de Tecnologias Alternativas da Zona da Mata (non-governmental organization) and the Federal University of Viçosa (UFV), who held actions in order to build the basis for agroecological transition, among which draws attention to the Interchange of Knowledge and Flavours, spaces for dialogue between agricultures on productive issues. It is noteworthy that, to raise the banner of agroecology, valuing the experiences of alternative production and marketing, were not only faced with all the force of the hegemony of agribusiness, but also the possibilities of transforming the reality of brazilian agriculture and agrarian space.